Transportation Mode Selection of UTHM Students: An Analysis Using Analytic Hierarchy Process - Mohd.Rashidi, Nur Fatin Nadiah; Che Him, Norziha; Abd Latif, Noor Azliza; Yusof, Yusliandy (Enhanced Knowledge in Sciences and Technology, 2025)
This study investigates the transportation preferences and challenges faced by students of Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh Campus, focusing on three faculties: the Faculty of Applied Sciences and Technology, the Faculty of Engineering Technology, and the Centre of Diploma Studies. Using a survey distributed via Google Forms, data were collected from 375 respondents to achieve three objectives: to identify preferred modes of transportation, to determine the barriers influencing these choices, and to analyse transportation preferences using the Analytical Hierarchy Process (AHP). The findings reveal that buses are the most popular mode of transportation among students, followed by cars or carpooling, while walking and cycling remain the least favoured options due to safety concerns and infrastructure limitations. Safety was identified as the most significant barrier influencing transportation choices, followed by convenience, weather, travel time, and cost. AHP analysis further highlighted the bus as the most cost-effective option, while private vehicles were preferred for their convenience. These results emphasize the need for improved transportation services, such as more frequent bus schedules, expanded parking spaces, and enhanced cycling and pedestrian infrastructure. By addressing these challenges, the university can create a more efficient, sustainable, and accessible transportation system to meet the needs of its students.